Influence of the MgO grade in MgO‐C refractory material and steel melt temperature on the inclusion population in Al‐treated steel. Issue 2 (31st January 2022) - Kerber, Florian; Malczyk, Piotr; Stein, Volker; Schemmel, Thomas; Jansen, Helge; Aneziris, Christos G.
Abstract: The influence of two industrially fabricated MgO‐C specimens differing in the MgO grade of the used MgO raw material on the population of nonmetallic inclusions via immersion tests was investigated. The immersion tests were performed in molten, Al‐treated 42CrMo4 steel at 1600°C and 1680°C in a steel casting simulator for 30 min. The inclusion population remaining within the solidified steel was characterized by the help of an EDS‐aided automated scanning electron microscope using an automated feature analysis. Several thousands of inclusions were detected and fully classified considering both their size and their elemental composition. The presented work reveals the impact of the MgO grade of the immersed MgO‐C specimens on the characteristics of the remaining nonmetallic inclusion population in dependency on the temperature of the molten steel. Significant differences in the total number of remaining inclusions and in regards to their size and species were exhibited and in‐depth analyzed. The paper contributes to the understanding of inclusion evolution mechanisms and propose potentially occurring phenomena based on the gained results.